Effects of Exogenous Boron on Salt Stress Responses of Three Mangrove Species - Jingjun Yang; Haihang Wei; Pifeng Lei; Jie Qin; Hongdeng Tian; Donghan Fan; Jihui Zhang; Zhenkai Qin; Xiaoying Huang; Xiu Liu (Plants)
Salt stress is common but detrimental to plant growth, even in mangroves that live in saline areas. Boron (B) is an essential micronutrient that performs an important role in many functions in plants; however, its protective role under salt stress is poorly understood, especially in long-lived woody plants. In this study, we conducted an indoor experiment under simulated tidal conditions with four treatments (10‰ salinity, 40‰ salinity, 40‰ salinity + 100 μM B, and 40‰ salinity + 500 μM B) and three mangrove species (Avicennia marina, Aegiceras corniculatum, and Bruguiera gymnorrhiza) to investigate the effects of exogenous B on salt tolerance in plant growth, morphology, physiology, and leaf anatomy. The results showed that exogenous low-concentration B treatment (100 μM B) improved the performance of mangrove species under high salinity stress, especially in terms of physiology and leaf anatomy, while high-concentration B treatment (500 μM B) had adverse effects. Additionally, we found that the response to exogenous B varied among species in physiology and leaf anatomy, such as proline, malondialdehyde, activity of antioxidant enzymes, palisade tissue, and spongy tissue, which may be related to the salt tolerance of different species. This study may provide useful insights into the alleviation of salt stress by B in mangrove growth and development, which may facilitate mangrove cultivation and afforestation in a saline environment.